Age-related difference in health care use and costs of patients with chronic kidney disease and matched controls: analysis of Dutch health care claims data. Issue 12 (9th October 2019) - van Oosten, Manon J M; Logtenberg, Susan J J; Leegte, Martijn J H; Bilo, Henk J G; Mohnen, Sigrid M; Hakkaart-van Roijen, Leona; Hemmelder, Marc H; de Wit, G Ardine; Jager, Kitty J; Stel, Vianda S
Abstract: Background: The financial burden of chronic kidney disease (CKD) is increasing due to the ageing population and increased prevalence of comorbid diseases. Our aim was to evaluate age-related differences in health care use and costs in Stage G4/G5 CKD without renal replacement therapy (RRT), dialysis and kidney transplant patients and compare them to the general population. Methods: Using Dutch health care claims, we identified CKD patients and divided them into three groups: CKD Stage G4/G5 without RRT, dialysis and kidney transplantation. We matched them with two controls per patient. Total health care costs and hospital costs unrelated to CKD treatment are presented in four age categories (19–44, 45–64, 65–74 and ≥75 years). Results: Overall, health care costs of CKD patients ≥75 years of age were lower than costs of patients 65–74 years of age. In dialysis patients, costs were highest in patients 45–64 years of age. Since costs of controls increased gradually with age, the cost ratio of patients versus controls was highest in young patients (19–44 years). CKD patients were in greater need of additional specialist care than the general population, which was already evident in young patients. Conclusion: Already at a young age and in the earlier stages of CKD, patients are in need of additional care with corresponding health care costs far exceeding those of the general population. In contrast to the general population, the oldest patients (≥75 years) of all CKD patient groups have lower costs than patients 65–74 years of age, which is largely explained by lower hospital and medication costs.